2009
DOI: 10.1143/jjap.48.067001
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Microwave Energy by a Spherical Nonmagnetic Metal Particle

Abstract: It is shown that scalar particle creation in the gravitational field of a massive object could OCCUI even if the radius of the object is larger than the Schwarzschild radius. Scalar field condensation could change the metric drastically, and decrease the observable mass of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…:7, m FeO ðrÞ¼ 0:2, d is the skin depth [10][11][12]. This indicates that the ohmic loss will be higher in the wustite phase (FeO¼Feþ1/2O 2 ).…”
Section: Resultsmentioning
confidence: 97%
“…:7, m FeO ðrÞ¼ 0:2, d is the skin depth [10][11][12]. This indicates that the ohmic loss will be higher in the wustite phase (FeO¼Feþ1/2O 2 ).…”
Section: Resultsmentioning
confidence: 97%
“…The amount of induction Joule heating in a non-magnetic metal nanoparticle is expressed as 1 30 l 2 0 rR 5 x 2 H 2 0 [26][27][28]. Here, l 0 is the permeability of free space, r is the electrical conductivity of metal, R is the radius of nanoparticle, x is the angular frequency, and H 0 is the magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of particle shape on MW absorption at different frequencies was predicted by Mie's theory, with the effects of spherically shaped particles being determined theoretically [18][19][20]. Ignatenko et al have previously reported that when considering the energy loss of these materials in a MW field, it is not possible to ignore the effect of the magnetic component and still achieve a good correlation between the analytical solution and experimental results [21,22].…”
Section: Influence Of Particle Shape On Mw Absorptionmentioning
confidence: 99%